2006
DOI: 10.1159/000088852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Dichotic Multiple-Stimulus Auditory Steady-State Responses in High-Risk Newborns and Young Children

Abstract: Experience with dichotic multiple-stimulus auditory steady-state responses (ASSRs) in clinical practice is described. ASSR thresholds were assessed in a sample of 60 high-risk newborns and young children between birth and 4 years of age. Amplitudes and signal-to-noise ratios (SNRs) of the ASSR were compared between normal-hearing infants and adults. Age-related changes within a group of infants younger than 3 months of age were investigated. A comparison was made between ASSR, the click-evoked auditory brainst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
99
6
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 67 publications
14
99
6
14
Order By: Relevance
“…Analysis of the ASSR in our complete series showed that the mean minimum response was 13.8 dBHL (26.4 dBSPL) at 2 kHz. These data concur with other published results 11,20,23,26 . Very few studies have compared thresholds measured with tone burst ABR and ASSR in the same population 6,15,17,19,27 .…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Analysis of the ASSR in our complete series showed that the mean minimum response was 13.8 dBHL (26.4 dBSPL) at 2 kHz. These data concur with other published results 11,20,23,26 . Very few studies have compared thresholds measured with tone burst ABR and ASSR in the same population 6,15,17,19,27 .…”
supporting
confidence: 94%
“…An additional issue is that most studies of these tests in children have been done with all subjects (or part of them) under sedation 3,[7][8][9][10][11][12][13][14][15][16][17] . A few studies of infants in natural sleep and adults have chosen one of the ears randomly 6,16,[18][19][20][21] or by recording the responses in two channels 22 .…”
Section: Discussionmentioning
confidence: 99%
“…For modulated stimuli, recording of responses to multiple simultaneous stimuli is possible John et al 1998). ASSRs are used to predict hearing thresholds in adults (Rance et al 1995) as well as in infants (Rance and Rickards 2002;Luts et al 2006;Alaerts et al 2009), where correlations with behaviorally determined thresholds exceed 0.95. Menard et al (2004) described electrically evoked auditory steady state responses (EASSRs) in cochlear implant (CI) subjects.…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore great interest in the clinical audiology community in the development of objective techniques to measure various hearing abilities that do not require behavioural responses from the patient and are able to determine fitting parameters for hearing aids and cochlear implants. While the use of cortical responses is in development (Billings et al 2007(Billings et al , 2011Carter et al 2010;Billings et al 2012;Chang et al 2012), transient brainstem responses and steady state responses (Luts et al 2004(Luts et al , 2006Alaerts et al 2010) are already used in clinical practice to objectively assess hearing thresholds in young children. However, while these measures provide an estimate of audibility with the prescribed hearing aid gain, they do not provide any indication of the expected hearing ability of the patient.…”
Section: Introductionmentioning
confidence: 99%